Adjuvant treatment improves overall survival in women with high-intermediate risk early-stage endometrial cancer with lymphovascular space invasion. Issue 11 (7th August 2020) - Son, Ji; Chambers, Laura M; Carr, Caitlin; Michener, Chad M; Yao, Meng; Beavis, Anna; Yen, Ting-Tai; Stone, Rebecca L; Wethington, Stephanie L; Fader, Amanda N; Burkett, Wesley C; Richardson, Debra L; et al.
Abstract : Background: Adjuvant therapy in early-stage endometrial cancer has not shown a clear overall survival benefit, and hence, patient selection remains crucial. Objective: To determine whether women with high-intermediate risk, early-stage endometrial cancer with lymphovascular space invasion particularly benefit from adjuvant treatment in improving oncologic outcomes. Methods: A multi-center retrospective study was conducted in women with stage IA, IB, and II endometrial cancer with lymphovascular space invasion who met criteria for high-intermediate risk by Gynecologic Oncology Group (GOG) 99. Patients were stratified by the type of adjuvant treatment received. Clinical and pathologic features were abstracted. Progression-free and overall survival were evaluated using multivariable analysis. Results: 405 patients were included with the median age of 67 years (range 27–92, IQR 59–73). 75.0% of the patients had full staging with lymphadenectomy, and 8.6% had sentinel lymph node biopsy (total 83.6%). After surgery, 24.9% of the patients underwent observation and 75.1% received adjuvant therapy, which included external beam radiation therapy (15.1%), vaginal brachytherapy (45.4%), and combined brachytherapy + chemotherapy (19.1%). Overall, adjuvant treatment resulted in improved oncologic outcomes for both 5-year progression-free survival (77.2% vs 69.6%, HR 0.55, p=0.01) and overall survival (81.5% vs 60.2%, HR 0.42, p<0.001). After adjusting for stage, grade 2/3, and age, improved progression-free survival and overall survival were observed for the following adjuvant subgroups compared with observation: external beam radiation (overall survival HR 0.47, p=0.047, progression-free survival not significant), vaginal brachytherapy (overall survival HR 0.35, p<0.001; progression-free survival HR 0.42, p=0.003), and brachytherapy + chemotherapy (overall survival HR 0.30 p=0.002; progression-free survival HR 0.35, p=0.006). Compared with vaginal brachytherapy alone, external beam radiation or the addition of chemotherapy did not further improve progression-free survival (p=0.80, p=0.65, respectively) or overall survival (p=0.47, p=0.74, respectively). Conclusion: Adjuvant therapy improves both progression-free survival and overall survival in women with early-stage endometrial cancer meeting high-intermediate risk criteria with lymphovascular space invasion. External beam radiation or adding chemotherapy did not confer additional survival advantage compared with vaginal brachytherapy alone.